63 Daily activity per minute slept drops with renal impairment in patients with chronic stable heart failure. (28th September 2016) - Egom, E; Pharithi, R; Jago, A; Fahy, S; Fall, S; Cagney, F; Maher, V; Maher, A
Abstract : Background: Optimal sleep may replenish energy levels and improve functional capacity. Daily activity levels per minute slept may reflect the efficiency of nocturnal energy storage. It is not known what factors may influence this relationship and whether it affects functional capacity. Objective: We evaluated what factors were related to nocturnal energy storage in patients with chronic stable heart failure. Methods: 105 consecutive patients with chronic Heart failure participated. We evaluated patients activity and sleep levels using FitBit Activity trackers. From this it was possible to calculate the average number of steps taken daily per minute slept at night. We also assessed NYHA and 6 minute walk distances, body composition, diet and cardiac parameters. Results: 76 men and 29 women, avg 67 years were enrolled. Steps per minute slept correlated significantly with age (r = −0.43***), eGFR (r = 0.36**), BNP (r = −0.36**), 6 min walk distance (r = 0.46***) NYHA (r = −0.23*), protein intake (r = 0.29**), Fat free Mass (r = 0.25*), Total body water (r = 025*), LV ejection fraction (ns ) and LV diameter (ns). However estimated GFR (**) was the only significant parameter in a multivariate analysis to correlate with nocturnal energy storage in these patients. N.B (ns = not significant) p < 0.05*, p < 0.01**, p < 0.001*** Conclusion: Our results highlight that in patients with chronic stable heart failure, renal function may determine nocturnal muscle energy storage and subsequent functional capacity in patients with heart failure.